Registration of 'S14‐9017GT' soybean cultivar with high yield, resistance to multiple diseases, and high seed oil content. Issue 3 (22nd September 2020) - Chen, P.; Shannon, G.; Ali, M. L.; Scaboo, A.; Crisel, M.; Smothers, S.; Clubb, M.; Selves, S.; Vieira, C. C.; Mitchum, M. G.; Nguyen, H. T.; Li, Z.; et al.
Abstract: 'S14‐9017GT' (Reg. no. CV‐536, PI 693755) is a Maturity Group V high‐yielding glyphosate‐tolerant soybean [ Glycine max (L) Merr.] cultivar developed and released in 2017 by the University of Missouri–Fisher Delta Research Center Soybean Breeding Program. S14‐9017GT was developed by conventional breeding from a cross between 'LD07‐3419' and 'S08‐9727RR1'. The parent S08‐9727RR1 is a breeding line that carries the GTS 40‐3‐2 transgene discovered by Monsanto Co. The other parent, LD07‐3419, is a breeding line developed by the University of Illinois soybean breeding program. Before release, S14‐9017GT was tested in 122 environments in Missouri and other southern states from 2015 to 2018 for yield and other agronomic traits. On average, S14‐9017GT yielded 4, 314 kg ha −1, which is higher than the mean of all the tests, which was 4, 124 kg ha −1 . S14‐9017GT seed contains 378 g kg −1 protein and 246 g kg −1 oil on a dry seed weight basis. It exhibits a relative maturity of 5.3, determinate growth habit, white flowers, light tawny pubescence, and tan pod wall. It has yellow seed with intermediate luster and black hila and a seed weight of 14.9 g per 100 seed. Plants of S14‐9017GT are 81 cm tall with resistance to lodging. It is resistant to stem canker, frogeye leaf spot, cyst nematode (races 1, 2, 3, and 5), reniform nematode, peanut root‐knot nematode, and sudden death syndrome and has field tolerance to phytophthora root rot. In addition to its high yield potential, high seed oil content, and broad adaptation across southern states, S14‐9017GT is also a suitable alternative for farmers who want to grow and save seed of glyphosate‐tolerant soybean cultivars.